Bovine Science Challenges and Advances - Abubakar, Muhammad (IntechOpen, 2022)
Bovine Science - Challenges and Advances presents up-to-date knowledge of bovine health, covering both introductory topics and more advanced concepts. Chapters cover such topics as new techniques in bovine science and development, health and risk factors and diagnosis of disease in bovines, and production and reproductive technologies and advancements.